Doxastic Voluntarism: A Sceptical Defence - Frederick, Danny (International journal for the study of skepticism, 2013)
Doxastic voluntarism maintains that we have voluntary control over our beliefs. It is generally denied by contemporary philosophers. I argue that doxastic voluntarism is true: normally, and insofar as we are rational, we are able to suspend belief and, provided we have a natural inclination to believe, we are able to rescind that suspension, and thus to choose to believe. I show that the arguments that have been offered against doxastic voluntarism fail; and that, if the denial of doxastic voluntarism is part of a strategy to defeat scepticism, it is inept, because knowledge presupposes doubt.